Current status and influential factors associated with adherence to self-monitoring of blood glucose with type 2 diabetes mellitus patients in grassroots communities: a cross-sectional survey based on information-motivation-behavior skills model in China - Lin, Manxin; Chen, Tingting; Fan, Guanhua (Frontiers in Endocrinology, 2023)
Objective: Self-monitoring of blood glucose (SMBG) plays a vital role in the maintenance of blood glucose with type 2 diabetes mellitus(T2DM) and pre-diabetes patients. The study was intended to describe the current status of SMBG with T2DM and pre-diabetes patients in grassroots communities, explore the relationship between SMBG frequency and blood glucose level and apply information-motivation-behavior (IMB) model to analyze the potential influencing factors of SMBG compliance based on electronic questionnaires. Methods: A cross-sectional study was conducted with 1388 T2DM and pre-diabetes patients who completed electronic questionnaires composed of demographics and IMB model content. Chi-square test, Mann-Whitney U test and multivariable logistic regression model analysis were utilized to explore deeply causes of SMBG compliance. Results: The study results demonstrated that only 26.2% (363/1388) of the 1388 patients were up to standard of adherence to SMBG that remained to rise. Patients with fixed occupation (OR=1.989, P=0.035), BMI in normal range (OR=1.336, P=0.049), smoking habit(OR=1.492, P=0.019), understanding SMBG frequency (OR=1.825, P<0.001), understanding control goal of blood glucose (OR=1.414, P<0.001), knowing all the functions of the blood glucose meter (OR=1.923, P<0.001), buying a blood glucose meter/test paper conveniently(OR=2.329, P=0.047), taking supplementary measurement when forgetting blood glucose test(OR=2.044, P=0.005), rotating all the fingers when measuring blood glucose (OR=1.616, P<0.001) and less pain at the needling site(OR=2.114，P<0.001）were independently promoting factors of adherence to SMBG. However, the lack of accessibility and convenience of blood glucose meter or heavy financial burden were blocking factors of adherence to SMBG. Moreover, there were still bottlenecks such as lack of health care knowledge and needle pricking pain. Conclusion: This study verified the practicability of applying IMB model to SMBG with T2DM and pre-diabetes patients. Adherence to SMBG still remained to improved, and putting more emphasis in improvement of individual information, motivation and behavioral skills with patients might be beneficial to maintain better adherence to SMBG in long-term routine of diabetes self-management.